Prevalence of pain-free weeks in chiropractic subjects with low back pain - a longitudinal study using data gathered with text messages - Lemeunier, Nadège; Kongsted, Alice; Axén, Iben (Chiropractic & manual therapies, 2011)
The use of automated text messages has made it possible to identify different courses of low back pain (LBP), and it has been observed that pain often fluctuates and that absolute recovery is rather rare. The purpose of this study was to describe the prevalence of pain-free weeks and pain-free periods in subjects with non-specific LBP treated by chiropractors, and to compare subjects from two different countries in these aspects. Data were obtained from two practice-based multicentre prospective outcome studies, one Danish and one Swedish, involving subjects being treated by chiropractors for non-specific LBP. Over 18 weeks, subjects answered a weekly automated text message question on the number of days in the past week that they had experienced bothersome LBP, i.e. a number between 0 and 7. The number of weeks in a row without any LBP at all ("zero weeks") as well as the maximum number of zero weeks in a row was determined for each individual. Comparisons were made between the two study samples. Estimates are presented as percentages with 95% confidence intervals. In the Danish and the Swedish populations respectively, 93/110 (85%) and 233/262 (89%) of the subjects were eligible for analysis. In both groups, zero weeks were rather rare and were most commonly (in 40% of the zero weeks) reported as a single isolated week. The prevalence of pain free periods, i.e. reporting a maximum of 0, 1 or 2, or 3-6 zero weeks in a row, were similar in the two populations (20-31%). Smaller percentages were reported for ≥ 7 zero weeks in a row. There were no significant differences between the two study groups. It was uncommon that chiropractic subjects treated for non-specific LBP experienced an entire week without any LBP at all over 18 weeks. When this occurred, it was most commonly reported for brief periods only. Hence, recovery in the sense that patients become absolutely pain free is rare, even in a primary care population.